IMPLEMENTASI KEBIJAKAN KUOTA BAGI PENYANDANG DISABILITAS UNTUK MENDAPATKAN PEKERJAAN DI KOTA YOGYAKARTA - Utami Dewi (NATAPRAJA, 2015)
This article aims to describe the implementation of the quota policy 1 percent ofemployment opportunities for persons with disabilities in the city of Yogyakarta as stated in Government Regulation No. 43 Year 1998 on Efforts to Increase Social Welfare of Persons with Disabilities. In addition, a study of the obstacles encountered and efforts made by the Government of the city of Yogyakarta is also a goal of writing this article. The method used in this research is qualitative descriptive. The author uses interview, observation and documentation for data collection. The results showed that the implementation of the quota policy 1 percent for disabled for agencies that have hired employees more than 100 people, has not run optimally in the city of Yogyakarta. This is demonstrated by the limited number of disabled absorbed in government and private agencies. Various obstacles encountered in the implementation of this policy, namely: training materials for the disabled less up to date, enforcement of regulations about 1 percent quota has not run optimally; low awareness of state agencies and private companies to employ persons with disabilities; and the lack of willingness of the disabled to find jobs.Keywords: Quota Policy, Employment, Disabled